Android-Based Quiz Game Development Using Quizizz for Fourth Grade Students at SDN Catak Gayam 1 Mojowarno - Tri Amelia, Risky; Nuruddin, Muhammad (IJPSE : Indonesian Journal of Primary Science Education, 2021)
Developments in the field of technology, especially education, are very influential in life. Educators as one of the main factors in supporting the quality of education must be able to utilize the types of media in an effort to carry out learning innovation strategies. The type of media that can support learning activities is the androidbased quiz game media using quizizz. This quiz game research is a development research. The android-based quiz game using quizziz has the purpose of knowing the design of android-based quiz game development using quizizz, the application of android-based quiz game products using quizizz, and the effectiveness of androidbased quiz games using thematic subjects. This research procedure uses a 4D model, namely define, design, development, and dissemination. SDN Catakgayam 1 Mojowarno was the location chosen to carry out research on a large scale, with 15 students enrolled in the 2020/2021 academic year. The techniques used in this study include media expert validation, material expert validation, RPP expert validation, student response expert validation, and documentation. Analysis of the data used is descriptive analysis. The results of the research on the application of quiz games obtained a total score of 87% which was validated by media experts, material experts and RPP experts. The validation contains media expert validation with a value of 92% which is very good, material expert validation 84% which is very good, RPP expert validation gets a score of 86% which is very good. Meanwhile, the effectiveness of the android-based quiz game obtained a total score of 82% which included student understanding with a value of 81.6% which was very good and student interest obtained a score of 82.5% which was very good. So it can be concluded, that an android-based quiz game using quizizz is stated to be very effective in supporting the learning activities of fourth grade students at SDN Catakgayam 1 Mojowarno.